PROBLEMS OF WOMEN ENTREPRENEURS - WITH SPECIAL REFERENCE TO TAILORS IN ASARIPALLAM, KANYAKUMARI DISTRICT - C.Subathra (International Journal of Research -GRANTHAALAYAH, 2017)
There is no doubt that we are in the midst of a great revolution in the history of women. Women are major contributions to the 21’st century’s emerging economy. These days the mantra that women seem to embrace is that of women entrepreneurship. Everywhere problem also travels along with prospect. Entrepreneurship is of no exception to this. The condition will be more serious especially with the womenfolk considered. In this paper, the researcher has attempted to study the problems of women entrepreneurs in general and the problems of women tailor in Asaripallam area in particular. Also suggested some valuable solutions to overcome those problems.